FIXED POINT FOR MAPPINGS SATISFYING KANNAN TYPE INEQUALITY IN FUZZY METRIC SPACES INVOLVING T-NORMS WITH EQUI-CONTINUOUS ITERATES - Dutta, P. N.; Choudhury, B. S.; Das, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
In this paper, we define coupled weak compatible condition and use it to derive certain coupled coincidence point theorems for four mappings in fuzzy metric spaces. We use here a t-norm which has equicontinuous iterates at 1. Some coupled fixed point results in metric spaces are obtained by applications of the results. Our results are obtained without any assumption of continuity on the mappings. Our main result is supported by an illustrative example. Some corollaries are also obtained.